Effects of soy plus zinc supplementation on growth and kidney health in Wistar rats: Implications for childhood stunting prevention - Yuniastini Yuniastini; Purwati Purwati; Antun Rahmadi; Sulastri Sulastri; Wien Wiratmoko; Iradah Lia Prasetio; Hendri Busman; Muhammad Al Hafidz; Fannia Khairani Mz; Mohammad Hafid Hak (Intelektual Pustaka Media Utama, 2026)
Zinc deficiency can cause growth and health problems, whereas protein from soy sources contributes to essential nutritional intake. This study aimed to evaluate the effects of soy plus zinc (SPZ) supplementation on growth and kidney health in Wistar rats. This study used a randomized controlled trial design with 24 rats divided into five treatment groups, including a control group. SPZ supplementation was administered daily for 14 days with varying zinc doses (0.020 mg and 0.035 mg per gram of body weight) and palatability enhancement using vanilla flavoring. Data obtained through measurements of initial and final body weights and kidney weights were analyzed using ANOVA to determine significant differences between groups. The results showed that SPZ supplementation positively contributed to growth, as evidenced by a significant increase in the final weight of rats compared to their initial weight (p < 0.05). Histological analysis of the kidneys indicated no visible structural damage, and the average increase in kidney weight was approximately 26.5%. The combination of soy and zinc in SPZ was shown to have a synergistic effect that benefits the development and kidney health of rats, demonstrating its potential application in the context of animal nutrition.